Table 2_Intergroup relations and dynamics of (dis)integration between youth with immigrant and non-immigrant origins: a scoping review.docx - Katja Lötjönen (22687091) (2025)
In light of growing societal diversity, gaining a deeper understanding of intergroup relations is increasingly crucial for fostering inclusive and cohesive communities. This scoping review synthesizes research on immigrant and non-immigrant young people’s perceptions and experiences of intergroup relations and (dis)integration. Analyzing 46 studies conducted between 2010 and 2023 through qualitative content analysis identified that intergroup contact theory and social identity theory are the dominant frameworks with quantitative methods being the most common. Seventeen thematic categories were produced, with the top four being (1) social inclusion or exclusion, (2) cultural or ethnic identity, (3) intergroup contact, and (4) attitudes. While offering insights into young people’s perceptions of interethnic encounters, the review highlights gaps in empirical, methodological, and theoretical diversity. Future research is encouraged to expand existing frameworks, integrate qualitative and mixed-method approaches, and focus more on real-world intergroup and interethnic encounter settings, that potentially enhances understanding of youth meaning-making in diverse ethnic contexts. Focusing on schools as key contexts for intergroup encounters, this review highlights the need to support integrative practices and incorporate cross-cultural after-school programs to enhance educational inclusion. Systematic review registration This scoping review is registered on the Open Science Framework (OSF) website: https://osf.io/p2678/overview.